Strategic Management of The Faculty of Social Sciences and Law, State University of Surabaya, in Improving The Quality of Education during The Covid-19 Pandemic - Eva Hany Fanida; Meirinawati Meirinawati (Department of Public Administration, Universitas Negeri Surabaya, 2022)
This study aims to describe the efforts of the Faculty of Social Sciences and Law (FISH) of the State University of Surabaya (Unesa) in improving the quality of education during the Covid-19 pandemic within the framework of strategic management theory. This research was motivated by the fact that during the pandemic, lectures at universities switched to online and required students and lecturers to make quick adaptations that have the potential to impact the quality of education. This study uses a qualitative descriptive method. The focus of the research covers the strategic management process, which includes the phases of environmental observation, strategy formulation, strategy implementation, and evaluation. The research subjects were determined purposively by involving the heads of faculties, departments, and study programs within the FISH Unesa environment. The data analysis technique flow through data collection, data display, data reduction, and concluding. The results showed that the SWOT method was used in the environmental observation phase, specifically identifying the strengths and weaknesses of the institution's internal environment and identifying opportunities and threats to the institution's external factors. At the strategy formulation stage, a lecture strategy was set with the name Limited and Gradual Face-to-Face Lectures (PTMTB). This stage is carried out by preparing the room and health protocols. The implementation of this strategy was carried out starting with a survey via Google Form to students. Not all study programs hold PTMTB depending on the number of students who fill out the Google Form. The faculty carry out the evaluation stage with the Covid-19 Task Force. Based on the findings, several points can be suggested. The institution should make training plans for educational staff to increase competence, increase awareness of education staff to prioritize providing services for the community and increase lecturers number so that the ideal ratio between lecturers and students is met.